Dual Photoisomerization on Distinct Potential Energy Surfaces in a UV-Absorbing Rhodopsin - Hontani, Yusaku; Broser, Matthias; Luck, Meike; Weißenborn, Jörn; Kloz, Miroslav; Hegemann, Peter; Kennis, John T M (Journal of the American Chemical Society, 2020)
UV-absorbing rhodopsins are essential for UV vision and sensing in all kingdoms of life. Unlike the well-known visible-absorbing rhodopsins, which bind a protonated retinal Schiff base for light absorption, UV-absorbing rhodopsins bind an unprotonated retinal Schiff base. Thus far, the photoreaction dynamics and mechanisms of UV-absorbing rhodopsins have remained essentially unknown. Here, we report the complete excited- and ground-state dynamics of the UV form of histidine kinase rhodopsin 1 (HKR1) from eukaryotic algae, using femtosecond stimulated Raman spectroscopy (FSRS) and transient absorption spectroscopy, covering time scales from femtoseconds to milliseconds. We found that energy-level ordering is inverted with respect to visible-absorbing rhodopsins, with an optically forbidden low-lying S1 excited state that has Ag- symmetry and a higher-lying UV-absorbing S2 state of Bu+ symmetry. UV-photoexcitation to the S2 state elicits a unique dual-isomerization reaction: first, C13═C14 cis-trans isomerization occurs during S2-S1 evolution in <100 fs. This very fast reaction features the remarkable property that the newly formed isomer appears in the excited state rather than in the ground state. Second, C15═N16 anti-syn isomerization occurs on the S1-S0 evolution to the ground state in 4.8 ps. We detected two ground-state unprotonated retinal photoproducts, 13-trans/15-anti (all-trans) and 13-cis/15-syn, after relaxation to the ground state. These isomers become protonated in 58 μs and 3.2 ms, respectively, resulting in formation of the blue-absorbing form of HKR1. Our results constitute a benchmark of UV-induced photochemistry of animal and microbial rhodopsins.